Faktor-faktor risiko Diabetes Melitus di Institut Pediatrik Hospital Kuala Lumpur - Chong, C.K.; Lailatul Akmal M.N.,; Mohd Johar J.,; Nor Azura A.G.,; Shahrum H.A.,; Tan, H.T.; V.Selvaraja.,; Zaleha J., (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 1995)
A case control study was conducted to identify the influence of risk factors such as overweight, history of viral infection, abnormal delivery, past family history of diabetes mellitus (DM) and history of maternal diabetes on the prevalence of DM among children. Information on 43 cases of DM among children under 15 years old, who have had treatment from the Endocrine Clinic UKM Specialist Clinic, between 1990 and 1994 were obtained from the